2013
DOI: 10.1002/jpln.201300281
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus bioavailability of biochars produced by thermo‐chemical conversion

Abstract: Recycling of P is a common strategy in efficient use of P. The aims of our investigation were to study the P extractability of biochars produced by low temperature conversion and to determine the effect of soda application on low‐temperature conversion of organic compounds and the bioavailability of P to rye grass (Lolium perenne L., cv. Grazer). In this study canola cake, dried distillers grains with solubles, and meat‐and‐bone meal were converted to biochars with thermo‐chemical conversion at 400°C. The P av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Another option is to produce a P rich biochar via pyrolysis (Shafizadeh 1982 ; Wang et al 2014 ; Weber et al 2014 ) or gasification (Schmieder et al 2000 ; Wu 2013 ). Pyrolysis is a process in which organic matter is heated indirectly to a temperature of 300–550 °C in the absence of oxygen.…”
Section: P Recovery From Waste Streamsmentioning
confidence: 99%
“…Another option is to produce a P rich biochar via pyrolysis (Shafizadeh 1982 ; Wang et al 2014 ; Weber et al 2014 ) or gasification (Schmieder et al 2000 ; Wu 2013 ). Pyrolysis is a process in which organic matter is heated indirectly to a temperature of 300–550 °C in the absence of oxygen.…”
Section: P Recovery From Waste Streamsmentioning
confidence: 99%
“…Despite generally comparatively low concentrations of available P in biochar, some studies did show that certain biochar can be used as P-fertiliser with high agronomic efficiencies, in some instances even performing better than mineral fertilisers (Wang et al, 2012;Weber et al, 2014). 4.3.6 Effect of biochars on germination and early seedling growth…”
Section: (Percentage) Availability Of P In Biocharmentioning
confidence: 99%
“…High-temperature of pyrolysis during charring animal bones may overcome this problem through incineration and heat sterilization (European Union, 2002;Chaala & Roy, 2003;Jeng et al 2006;Cascarosa et al, 2012). Warren et al (2009), Weber et al (2014), El-Refaey et al (2015), Zwetsloot et al, (2014 and2016); Buss et al (2016) have shown that P in bone char is as effective as mineral P fertilizers besides being more economic alternative. X-ray diffraction patterns of bone char and phosphate rock displayed evident similarities and pointed out to the analogy between the structures of PR-apatite and bone char -apatite mineral.…”
Section: Evaluation Of Poultry Manure and Acidified Water For Improvimentioning
confidence: 99%